The microbiome landscape in pediatric Crohn’s disease and therapeutic implications - Fetter, Karin; Weigel, Markus; Ott, Benjamin; Fritzenwanker, Moritz; Stricker, Sebastian; de Laffolie, Jan; Hain, Torsten; Justus Liebig University Giessen (My University, 2023)
Dysbiosis of the gut microbiome and a pathological immune response in intestinal tissues form the basis of Crohn’s disease (CD), which is a debilitating disease with relevant morbidity and mortality. It is increasing in childhood and adolescents, due to western life-style and nutrition and a large set of predisposing genetic factors. Crohn’s disease-associated genetic mutations play an essential role in killing pathogens, altering mucosal barrier function, and protecting the host microbiome, suggesting an important pathogenic link. The intestinal microbiome is highly variable and can be influenced by environmental factors. Changes in microbial composition and a reduction in species diversity have been shown to be central features of disease progression and are therefore the target of therapeutic approaches. In this review, we summarize the current literature on the role of the gut microbiome in childhood, adolescent, and adult CD, current therapeutic options, and their impact on the microbiome.
Keywords: Crohn’s disease; inflammatory bowel disease; gut microbiome; dysbiosis; pediatrics; children; adolescents; ddc:570